2013
DOI: 10.17816/rcf11217-25
|View full text |Cite
|
Sign up to set email alerts
|

Neuronoprotective action of cortexin andcortagen

Abstract: РезюмеИзучены изменения внутриклеточных потенциалов покоя и действия идентифицированных нейронов пе-дальных ганглиев ЦНС моллюска Planorbarius corneus, зарегистрированные с помощью внутриклеточных микроэлектродов и ионных токов изолированных нейронов при фиксации потенциала под влиянием официнального препарата кортексина (кортексина 0,5-1000 мкг/мл и глицина от 4-4000 мкМ), пептидов кортексина (0,5-1000 мкг/мл), глицина (0,5 и 5 мМ) и тетрапептида кортагена (0,1-10 000 мкМ). Показа-но, что препарат кортексина … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…and F. stylosa Lingelsh. It has been indicated that Cortex Fraxini possesses various pharmacological effects, including anti-pathogenic [ 1 ], anti-inflammatory [ 2 ], analgesic [ 3 ], anti-cancer [ 4 ], antioxidative stress [ 5 ], neuroprotective [ 6 ] and vascular protective effects [ 7 ]. There are many active ingredients in Cortex Fraxini .…”
Section: Introductionmentioning
confidence: 99%
“…and F. stylosa Lingelsh. It has been indicated that Cortex Fraxini possesses various pharmacological effects, including anti-pathogenic [ 1 ], anti-inflammatory [ 2 ], analgesic [ 3 ], anti-cancer [ 4 ], antioxidative stress [ 5 ], neuroprotective [ 6 ] and vascular protective effects [ 7 ]. There are many active ingredients in Cortex Fraxini .…”
Section: Introductionmentioning
confidence: 99%
“…Esculetin, 6,7-dihydroxycoumarin, is a coumarin subordinate found in different plants, Cortex fraxini is one of the generally utilized conventional Chinese prescriptions [1]. It has been shown that Cortex fraxini has different pharmacological impacts, including hostile to pathogenic [2], calming [3], analgesic [4], against malignant growth [5], antioxidative activity [6], neuroprotective [7], and vascular defensive impacts [8]. It is one of the fundamental dynamic elements of Cortex fraxini, has been used as expectorant, against tussive [9] cell reinforcement, hostile to bacterial, and hostile to tumor [10].…”
Section: Introductionmentioning
confidence: 99%